Management of Blood Pressure and Heart Rate in Chronic Kidney Disease - Kaltsatou, Antonia (Current Pharmaceutical Design, 2017)
Background: Hypertension is considered a major health problem in patients with chronic kidney disease (CKD) as approximately 80-85% of CKD patients’ suffer from hypertension in the United States. Hypertension is the second leading cause of CKD after diabetes and is strongly related to morbidity and mortality. It has been found that there is a relation among hypertension, glomerular filtration rate (GFR) and creatinine levels. Objective: Since there is a strong relation between hypertension and CKD, and hypertension seems to lead to cardiovascular diseases, which have epidemic proportions in CKD, this review article discusses the etiology of hypertension and the existing optimal therapies that contribute to the hypertension and heart rate management. Results: There are many approaches that contribute to the management of hypertension and heart rate in CKD patients. Lifestyle modifications in combination with drug therapy lead to the better control of hypertension in CKD patients. Conclusion: Hypertension is strongly related to cardiovascular diseases in CKD patients. Since this relation exists and hypertension leads to cardiovascular diseases, the management of hypertension and increased heart rate should be a main therapeutic target in these patients.
Keywords: heart rate